Influence of Water and Specific Anions and Cations on Physico-Chemical and Biological Properties of Soil - Jaya V (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
The availability of nutrients either present in the soil or applied as fertilizer is governed by various factors like the physical, chemical and biological reactions in the soil. The present investigation is undertaken to study the direct and interaction effects of different levels of phosphorus, sodium and water on the physic-chemical and biological properties of soil. An experiment is laid out in the farm area of College of Agriculture, Vellayani. The lay out is in randomised block design with 18 treatments and three replications. Banana var. Nendran is used as the test crop. The treatment combinations include, three levels of phosphorus (control, 90 and 115 g P2o5/plant/annum), three levels of sodium (control, 68 and 136 g Na/plant/annum) and two levels of water (20 and 40 per cent depletion from field capacity moisture condition). Soil and plant analysis are done for the elements, nitrogen, phosphorus, potassium, calcium, magnesium and sodium. Initial soil samples and samples collected at 90, 180 and 270 days after planting are used for different physic-chemical analysis. Physical properties such as moisture parameter, bulk density, particle density, porosity, water holding capacity, volume of expansion and aggregation are done for all the soil samples. Total nutrient contents and hydraulic conductivity for the soil samples collected at the final stage are also done. Plant samples collected at the harvest are analysed for total nitrogen, phosphorus, potassium, calcium, magnesium and sodium. Biometric parameters such as plant height, number of leaves, girth of pseudostem and leaf area index are observed and recorded during three stages. Mycorrhizal counting is carried out, during all the stages, considering as three seasons. All the data are statistically analysed and interpreted. Phosphorus at the highest dose is beneficial for all the biometric parameters studied. In the case of sodium, it has an adverse effect on the girth of the pseudostem, even at the highest level of phosphorus. Leaf area index is very high in the presence of sodium and phosphorus even at 40 per cent depletion from field capacity. Soil phosphorous and soil moisture are negatively correlated with mycorrhizal percentage during second and third stage. Plant phosphorous and sodium positively correlated with the mycorrhizal percentage. Even with moisture at 40 per cent deplection from field capacity and lower amounts of phosphorous applied, the uptake of phosphorous by the plant is increased by mycorrhizal association. Higher levels of phosphorous and sodium increase the waterholding capacity and volume of expansion. Bulk density and particle density give optimum values with medium levels of phosphorous and sodium. Moisture percentage increased in plots with optimum sodium than with plots receiving higher dose of water with no sodium. Lower water level reduces bulk density and particle density. The mean weight diameter which is a measure of soil aggregation is positively correlated with soil phosphorous and negatively correlated with soil moisture. Optimum dose of phosphorous and sodium favour hydraulic conductivity of soil. Medium dose of sodium and phosphorous increase organic carbon and soil available nitrogen. Lower level of water is sufficient for increasing soil available nitrogen, soil available phosphorous and organic carbon, in the presence of sodium. Positive correlation exists between soil available phosphorous and mycorrhizal percentage in the first stage. Maximum phosphorous is available during the second stage with a negative correlation with mycorrhiza. Optimum dose of sodium and high level of phosphorous, increase the availability of available potassium, exchangeable calcium, and exchangeable magnesium. There is a positive correlation exist between soil moisture and soil sodium. As the plant grows the soil available potassium decrease. Higher levels of water, increase, exchangeable calcium and magnesium also. Total nutrient content of nitrogen, phosphorous and potassium are decreased with increasing phosphorous, sodium and water, which is, because of their increased availability. Plant phosphorous is related with soil available phosphorous. For optimum dose of phosphorous, lower level of water and higher level of sodium, the availability and uptake of potassium is at the optimum. Positive correlation obtained for plant phosphorous with mycorrhiza, soil sodium, soil available phosphorous, and mean weight diameter. Plant sodium is also positively correlated with soil available phosphorous, mycorrhizal population, plant phosphorous and hydraulic conductivity. Highest level of phosphorous and water and medium level of sodium favour the uptake of calcium and magnesium. For increasing sodium availability, only optimum dose of phosphorous is required. Sodium at the optimum dose improve soil hydraulic properties. Optimum dose of phosphorous and sodium improves many of the physic-chemical properties of the soil. In the presence of mycorrhiza, even lower levels of phosphorous is sufficient to meet the plant requirement. With more levels of phosphorous, sodium and water, the study can extended in relation to plant growth. Yield factor is not considered in the present study.